Analysis of the Effect of Parenting Patterns on the Character in RA Al-Iqro Cigugurgirang - Roprop Latiefatul Millah; Hera Handayani; Sintya Rahma Fadillha; Meri Triapriliawati; Nur Antika Yulianti (UPI Kampus Cibiru, 2023)
Parenting is one of the parameters of how students' character is formed in early childhood. Problems that commonly occur in class stem from how the interactions occur between students. This study aims to determine the effects of parenting patterns on the character of early childhood with research in RA Al-Iqro, Cugugurgirang. The research method used is qualitative research with data collection methods through observation of children, interviews, and survey sheets through questionnaires to parents of students after going through a cycle of periodic observations. The results show that the achievement of indicators of children's character education, the sub-indicators of fairness and leadership spirit as well as indicators of Good and humility, which is 61%, the highest total achievement of children's character is at 97.22% with very well-developed criteria. Analysis of parenting patterns that seek to shape, control, and evaluate the attitudes and behavior of their children following the rules of parents, 94% for parenting always give love and affection sincerely to children, and with. Different parenting styles will determine the character of the child, which will have a direct and significant impact on the child's learning process.